ICU Cornerstone: Changing our view of blood transfusions - Lee, Warren L (BioMed Central, 2002)
Blood transfusions are commonly administered to critically ill patients, but deciding when to transfuse a particular patient is often difficult and necessitates careful consideration of both the potential benefits and risks. This commentary briefly discusses some of the considerations both for and against blood transfusion in the setting of critical illness and reviews a landmark clinical trial in this area. Finally, we reflect on the changes in attitudes towards the transfusion of blood and blood products that have taken place over the last 20 years.